Survey Hambatan Mahasiswa dalam Mencari Bantuan Psikologis - Susilawati Susilawati; Endang Rifani; Weni Anggraini (Kuras Institute, 2022)
Mental health of university students has recently become a topic of attention by mental health researchers, in addition to having a significant urgency in daily life, mental health is a determining factor in achieving effective living. This study aims to determine the level of obstacles experienced by students in the process of seeking professional psychological assistance. This study uses a quantitative method obtained through survey techniques with descriptive analysis explore using SPPS assistance, by providing a psychological scale that is distributed via google form, the respondents of this study are college students. The results of the study show that students have a high level of barriers in seeking psychological professional help. Discussions and suggestions are in the script.